2017
DOI: 10.3947/ic.2017.49.1.51
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Virulence Factors Among ClinicalEnterococcus faecalisIsolates in Southwestern Iran

Abstract: BackgroundOver the past two decades, enterococci have emerged as an important agent responsible for hospital acquired infection. Several virulence factors contribute to the adherence, colonization, evasion of the host immune response, and pathogenicity and severity of the infection. Enterococcus faecalis is the most common and virulent species causing infections in hospitalized patients. The aim of the present study was to examine the prevalence of genes encoding virulence factors and antimicrobial resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
5
25
3
Order By: Relevance
“…Like in this study, the HLGR was reported high in other similar studies from Iran, (Emaneini et al 2016;Heidari et al 2017). The studies conducted in other countries have also been reported a high rate of the HLGR phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…Like in this study, the HLGR was reported high in other similar studies from Iran, (Emaneini et al 2016;Heidari et al 2017). The studies conducted in other countries have also been reported a high rate of the HLGR phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…As reported earlier, hyl was detected only in E. faecium [33]. Nevertheless, a few studies have reported the incidence of hyl in both species [29,[34][35][36][37][38][39]. Significant difference was observed in the VF score between species.…”
Section: Discussionmentioning
confidence: 54%
“…Nevertheless, the presence of virulence determinants in the clinical isolates might contribute to increased severity as they could be expressed under optimum conditions in vivo. Metadata of the previous studies on the detection of virulence genes of enterococci by multiplex/duplex/simplex PCR is depicted in Additional file 1: Table S1 [18,27,29,[33][34][35][36][37][38][39][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…E. faecalis, likely through multiple virulence factors that may involve in its colonization, survival, and pathogenicity, promote disease in the urinary tract. Heidari and et al investigated the incidence of genetic virulence markers among clinical E. faecalis and found that occurrence of multiple virulence factors was common in the urinary tract isolates, while most of the strains carried predominantly four, ve and seven virulence determinants in HA-UTIs [33]. Aberna and Prabakaran investigated the presence of genetic virulence markers in E. faecalis and found that the occurrence of multiple virulence factors was common in the urinary tract isolates, while most of the strains carried predominantly two and three virulence determinants in HA-UTIs [24].…”
Section: Discussionmentioning
confidence: 99%